Profiles of entrepreneurs and their start-ups III the UPM-MTDC Incubation Center - Khairul Akmaliah Adham,; Maisarah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2004)
In this study, nine entrepreneurs whose companies were located in the UPM-MTDC Technology Incubation Center were interviewed. The objective was to examine certain key characteristics of the firms (those related to their business activities) and of the entrepreneurs (characteristics related to their motivations and demographic backgrounds). This study revealed a number of similarities between the characteristics of these entrepreneurs and the characteristics reported in studies of their counterparts in the us and the UK. Similarities included the common use of personal savings as sources of capital for starting up their businesses; the fact that start-up of the new ventures was initiated by entrepreneurial teams; problems in acquiring capital, particularly during their growth stage; and that all the entrepreneurs had at least a 4-year bachelors degree. Nevertheless, the study also revealed differences between business support services available at UPM-MTDC and those found in business incubators in the US. For example, compared to the incubators in the US, PM·MTDC does not provide many of the services required by a business, and there is a lack of utilization of university resources, as well as a lack of linkage with other resources and contacts in the industry in which a given business is working.